2001
DOI: 10.1121/1.1381539
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid BIE/FFP scheme for predicting barrier efficiency outdoors

Abstract: To assess the acoustical performance of noise screens in the presence of an arbitrary sound speed profile, a numerical scheme based on a combination of the boundary integral and fast field program methods is developed. The Green's function required in the boundary integral is evaluated by a fast field formulation. The procedure is validated by comparing its predictions with other numerical results for simple cases and with measurements for indoor model experiments simulating downward refracting conditions. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Q i = Q and θ ij =0, then the double summation in the last term of Equation (13) Figure 1 has already shown that the simplified Equation (10) has good agreement with direct realisations. The agreement between the simplified MCF prediction, Equation (13), and the full MCF method, Equation (12), is even better, as can be seen in Figure 2, which uses the same simulation cases of Figure 1. The scatter of data is much less in Figure 2 because of the deterministic nature of the MCF calculations.…”
Section: Mutual Coherence Function (Mcf)mentioning
confidence: 50%
See 1 more Smart Citation
“…Q i = Q and θ ij =0, then the double summation in the last term of Equation (13) Figure 1 has already shown that the simplified Equation (10) has good agreement with direct realisations. The agreement between the simplified MCF prediction, Equation (13), and the full MCF method, Equation (12), is even better, as can be seen in Figure 2, which uses the same simulation cases of Figure 1. The scatter of data is much less in Figure 2 because of the deterministic nature of the MCF calculations.…”
Section: Mutual Coherence Function (Mcf)mentioning
confidence: 50%
“…In these works, the boundary element method (BEM) [11] has been shown to be highly effective and accurate for predicting the insertion loss of barriers of complex shapes. BEM schemes that use special formulations of the Green's function to take into account of atmospheric refraction on sound propagation over a barrier have been proposed [12,13]. However almost all studies on complex shaped barriers do not consider the effect of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Another extension of the BEM, which accounts for a refracting atmosphere as well as a non-uniform boundary was introduced by Taherzade et al [40].…”
Section: B O U N D a R Y E Lem En T Ivlethodsmentioning
confidence: 99%